Three-Stage Forward and Closed Loop Supply Chain Models Under Consignment Stock Partnership - Alkhatib, Osama (2016)
A Master of Science thesis in Engineering Systems Management by Osama Alkhatib entitled, "Three-Stage Forward and Closed Loop Supply Chain Models under Consignment Stock Partnership," submitted in November 2016. Thesis advisor is Dr. Rami As'ad and thesis co-advisor is Dr. Moncer Hariga. Soft and hard copy available.